A Scalable MAC Protocol Supporting Simple Multimedia Traffic QoS in WSNs. (7th August 2011) - On, JeongSeok; Jeon, HahnEarl; Lee, Jaiyong
Abstract : Wireless sensor networks (WSNs) are a vibrant research field for the last several years. Especially, design of MAC protocols supporting multimedia traffic QoS is recent challenging work. However, the mechanisms of protocols that can guarantee multimedia traffic QoS have several problems in multihop wireless sensor networks. There are a lot of reasons, including limited end-to-end delay and high throughput. In this paper, we propose ascalable MAC protocol that guarantees multimedia traffic, still images, and scalar sensor data QoS in multi-hop wireless sensor networks. The MAC protocol has made it possible to transmit multimedia streaming traffic without a great change of the end-to-end delay for a specific time. And if there are the some link failures in multi-hop transmission, the protocol can recover the links quickly. Using this algorithm, the proposed MAC protocol outperforms the IEEE 802.11e EDCF and the IEEE 802.15.4 MAC protocol in terms of the end-to-end delay and stable transmission of multimedia streaming data.